Evaluation of the specialist palliative care team 'a colleagues perspective'. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Steele, Emma
Abstract : Background: Following the move of two hospitals into one large new hospital Queen Elizabeth Hospital, Birmingham the author was interested to reflect on the service Specialist Palliative Care Team provided for patients, carers and staff throughout the acute setting. Aims: The author proposed to collect views from referring staff to evaluate the work of the Specialist Palliative Care Team, to ascertain how accessible and effective the team are and main reasons for referral. The author also aimed to determine if the team is visible within clinical areas and look for areas of improvement and guidance for future working. Method: The author devised a set of questions designed to explore the opinions that health professional colleagues working within the Trust had about the Specialist Palliative Care Team. The author handed out five questionnaires to thirty clinical areas and asked any clinical staff to complete. Results: The analysis of the survey suggests that the Specialist Palliative Care Team does provide a good service and supports staff and patients. The team members generally respond to a referral within an appropriate timescale and recognise the referring health professionals skills. 89% of respondents felt that the team could provide more education and many suggested that the service could be extended to 7 days a week. 18 members of staff felt the teams communication skills were 'satisfactory' and 7% answered 'poor'. Conclusion: A number of themes arose for the Specialist Palliative Care Team to consider and discuss including provision of education, communication skills, extending the service and raising the teams profile.